Surgical Treatment of a Voluminous Median Nerve Lipofibromatous Hamartoma Involving Distal Forearm: A Case Report. Issue 2 (April 2021) - Pecchia, Stefano; Guzzini, Matteo; Koverech, Guido; Arioli, Leopoldo; Andreozzi, Valerio; Perugia, Dario
Abstract : Case: Lipofibromatous hamartoma (LFH) is a rare benign tumor of the peripheral nerves, which often affects upper extremity. There is no consensus regarding management of these lesions. We report a case of median nerve LFH in the volar forearm of a 24-year-old man with carpal tunnel syndrome symptoms. Clinically, the mass appeared tender to palpation, ill-defined and soft, located on the volar aspect of the left forearm. Open epineurotomy and neurolysis of the median nerve were performed with full recovery at 1 year. Conclusion: Surgical approach may be resolutive in patients with large masses refractory to conservative treatment.